Mindfulness and Work Engagement among Generation Y - Endro Puspo Wiroko; Evanytha Evanytha (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
One of the emerging concepts in occupational health psychology today is work engagement. The present study investigates work engagement among generation Y and its correlation to mindfulness. Work engagement is positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption. Mindfulness is present moment awareness with an observing and non-judging stance. This is the first study to examine the correlation between mindfulness and work engagement among generation Y, specifically in Indonesia. Participants of this study are 251 male and female generation Y working in some cities across Indonesia. They are 18 to 36 years old and they are varied in educational background as well as in job tenures. Data is gathered using two scales, namely Utrecht Work Engagement Scale and Mindful Attention Awareness Scale. Regression analysis reported that mindfulness contributes 2 percent to work engagement. Mindfulness is found to relate positively with work engagement (r= .142). Theoretical and practical implications are discussed.